The Routledge companion to creativity - Rickards, Tudor; Runco, Mark A.; Moger, Susan (London Routledge, 2009)
Creativity can be as difficult to define as it is to achieve. This is a complex and compelling area of study and this volume is perfectly poised to explore how creativity can be better understood, and used, in a range of contexts. The book not only centres on creativity in wider organizational theory, but also defines the conditions in which creativity can flourish, and assesses how the contemporary business environment has an impact on creative solutions.The volume grounds the concept of creativity in a sound theoretical framework and explores issues of practical and theoretical consequence covering a range of themes, including:innovation and entrepreneurshipcreativity and designenvironmental influencesknowledge managementmeta-theories of creativitypersonal creativitystructured interventions.Comprising contributions written by an unusually wide array of leading creativity scholars, The Routledge Companion to Creativity is an insightful and cutting edge resource. It is an essential purchase for anyone with an interest in creativity from a business, psychology or design perspective.